Cell Interaction Molecular and Immunological Basis for Disease Management - Singh, Bhawana (IntechOpen, 2021)
This book discusses contemporary ideas on different molecular and immunological aspects of diseases. Different signaling mediators drive the production of messenger molecules that mediate their action, leading to the elicitation/suppression of immune responses. It provides a balanced approach to the study of different molecular phenomena that eventually drive infection outcomes and that can be manipulated for therapeutic benefits.